The Use of a Penta-Deuterophenyl Substituent to Improve the Metabolic Stability of a Tyrosine Kinase Inhibitor - Júlia Dulsat; Raimon Puig de la Bellacasa; José I. Borrell (Molecules)
In cases in which a rapid metabolism is the cause of an unfavorable pharmacokinetic profile, it is important to determine the Sites of Metabolism (SoMs) of a molecule to introduce the necessary modifications to improve the stability of the compound. The substitution of hydrogen atoms by deuterium atoms has been proposed to ameliorate such properties due to the greater stability of the C-D bonds. IQS016, bearing a 2-phenylamino substituent, is a compound previously described by our group with good biological activity as a discoidin domain receptor (DDR2) inhibitor but suffers from low metabolic stability determined in a test with rat-liver microsomes (less than 50% of the initial compound after 60 min). We have obtained the corresponding 2-(penta-deuterophenyl) analog (IQS016-d5) from aniline-2,3,4,5,6-d5 showing that it has a better metabolic stability than IQS016 and a higher inhibitory effect on isolated tyrosine kinase receptors but not a better 2D in vitro effect.